Heterogeneity of magnitude, allergen immunodominance, and cytokine polarization of cockroach allergen‐specific T cell responses in allergic sensitized children. Issue 8 (13th October 2021) - da Silva Antunes, Ricardo; Sutherland, Aaron; Frazier, April; Schulten, Veronique; Pomés, Anna; Glesner, Jill; Calatroni, Agustin; Altman, Matthew C.; Wood, Robert A.; O'Connor, George T.; Pongracic, Jacqueline A.; Khurana Hershey, Gurjit K.; et al.
Abstract: Background: Characterization of allergic responses to cockroach (CR), a common aeroallergen associated with asthma, has focused mainly on IgE reactivity, but little is known about T cell responses, particularly in children. We conducted a functional evaluation of CR allergen‐specific T cell reactivity in a cohort of CR allergic children with asthma. Methods: Peripheral blood mononuclear cells (PBMCs) were obtained from 71 children, with mild‐to‐moderate asthma who were enrolled in a CR immunotherapy (IT) clinical trial, prior to treatment initiation. PBMC were stimulated with peptide pools derived from 11 CR allergens, and CD4+ T cell responses assessed by intracellular cytokine staining. Results: Highly heterogeneous responses in T cell reactivity were observed among participants, both in terms of the magnitude of cytokine response and allergen immunodominance. Reactivity against Bla g 9 and Bla g 5 was most frequent. The phenotype of the T cell response was dominated by IL‐4 production and a Th2 polarized profile in 54.9% of participants, but IFNγ production and Th1 polarization was observed in 25.3% of the participants. The numbers of regulatory CD4+ T cells were also highly variable and the magnitude of effector responses and Th2 polarization were positively correlated with serum IgE levels specific to a clinical CR extract. Conclusions: Our results demonstrate that in children with mild‐to‐moderate asthma, CR‐specific T cell responses display a wide range of magnitude, allergen dominance, and polarization. These results will enable examination of whether any of the variables measured are affected by IT and/or are predictive of clinical outcomes.